2013
DOI: 10.3109/14992027.2012.759665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the preliminary auditory profile test battery in an international multi-centre study

Abstract: The auditory profile forms a clinical test battery that is applicable in four different languages. Even after baseline correction, differences between test materials have to be taken into account when interpreting results of language-dependent tests in HI listeners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
64
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 49 publications
7
64
0
Order By: Relevance
“…Some of the HI listeners ( Ͻ 10%) found the test too hard to complete. MAA results from the preliminary auditory profi le test battery were closely comparable to previously published results ( Van Esch et al, 2013).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Some of the HI listeners ( Ͻ 10%) found the test too hard to complete. MAA results from the preliminary auditory profi le test battery were closely comparable to previously published results ( Van Esch et al, 2013).…”
supporting
confidence: 85%
“…A virtual version of the minimum audible angle (MAA) test was chosen (Mills, 1985;Hafter et al, 1992;Grantham et al, 2003). Van Esch et al (2013) reported a small learning effect but no signifi cant effect of test centre, and good correspondence between test and retest measurements. Some of the HI listeners ( Ͻ 10%) found the test too hard to complete.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…van Esch et al, 2013). An example of the questionnaire method can be found in the multi-dimensional speech, spatial, and qualities (SSQ) hearing scale (Gatehouse and Noble, 2004) Although this paper did not appear in the web of knowledge literature search, we felt that it was worth including given its potential use as a behavioural measure of listening effort and/or fatigue over time.…”
Section: Self-reported Listening Effortmentioning
confidence: 93%
“…Self-report judgments of effort are also used during experimental listening tasks. In one large-scale study, participants were asked to indicate (on a 100-point scale) how ' effortful ' they found each particular trial in an auditory profi le test battery (van Esch et al, 2013). As expected, hearing-impaired participants gave signifi cantly higher ' effort ' ratings than their normal-hearing counterparts in all listening conditions.…”
Section: Self-reported Listening Effortmentioning
confidence: 98%